2000
DOI: 10.1046/j.1364-3703.2000.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of the plant pathogenic ascomycete Leptosphaeria maculans; mapping mating type and host specificity loci

Abstract: A genetic and physical map has been developed for the loculoascomycete Leptosphaeria maculans, a pathogen of oilseed Brassicas. The genetic map was constructed from 58 F(1) progeny and comprises 155 amplified fragment length polymorphic (AFLP) markers, three random amplified polymorphic DNA (RAPD) markers, the mating type locus and a host specificity locus conferring the ability to form lesions on Brassica juncea. Twenty-one linkage groups, 5 pairs, and 18 unlinked markers were assigned, and the genome size wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 42 publications
0
51
0
Order By: Relevance
“…Recently, genetic linkage maps have been constructed for ascomycete pathogens causing canola blackleg (Leptosphaeria maculans) (Cozijnsen et al 2000), septoria tritici wheat blotch (Mycosphaerella graminicola) (Goodwin et al 2007), and banana black leaf streak (Mycosphaerella fijiensis) (Manzo-Sánchez et al 2008) diseases. Based on linkage analysis, molecular markers associated with genetic loci conferring mating type (Kema et al 2002;Kubisiak and Milgroom 2006;Kuhn et al 2006), host specificity, vegetative incompatibility (Kubisiak and Milgroom 2006) and avirulence (Kema et al 2002) have been reported.…”
mentioning
confidence: 99%
“…Recently, genetic linkage maps have been constructed for ascomycete pathogens causing canola blackleg (Leptosphaeria maculans) (Cozijnsen et al 2000), septoria tritici wheat blotch (Mycosphaerella graminicola) (Goodwin et al 2007), and banana black leaf streak (Mycosphaerella fijiensis) (Manzo-Sánchez et al 2008) diseases. Based on linkage analysis, molecular markers associated with genetic loci conferring mating type (Kema et al 2002;Kubisiak and Milgroom 2006;Kuhn et al 2006), host specificity, vegetative incompatibility (Kubisiak and Milgroom 2006) and avirulence (Kema et al 2002) have been reported.…”
mentioning
confidence: 99%
“…L. maculans is haploid, outcrossing, can be readily transformed, and has a genome size of about 34 Mb, which is similar to that of other ascomycetes (Kupfer et al, 1997). Its chromosomes are of a size range (about 0.7 to 3.5 Mb) and number (16) for optimal resolution by electrophoretic karyotyping (Taylor et al, 1991;Howlett, 1997;Cozijnsen et al, 2000).…”
Section: Genetic and Physical Mappingmentioning
confidence: 98%
“…Another cotyledonary avirulence gene, alm1, has been mapped by a research group at University of Wisconsin (Madison, WI) (Pongam et al, 1998). The mapping of this gene, as well as that of a gene conferring the ability to attack both cotyledons and stems of B. juncea Cozijnsen et al, 2000) is discussed later. The presence of a small number of loci controlling (a)virulence is suggested by a study of environmental and genetic components of variance in the virulence of 24 Australian isolates of L. maculans on five B. napus cultivars (Pang and Halloran, 1996).…”
Section: Host-pathogen Interactionsmentioning
confidence: 98%
See 2 more Smart Citations